Influence of coal blending on ash fusion property and viscosity. (1st February 2017) - Wang, Dachuan; Liang, Qinfeng; Gong, Xin; Liu, Haifeng; Liu, Xia
Abstract: Coal blending is a practical method to reduce ash percentage and improve fusion properties for gasifiers. High viscosity coal was investigated to improve its ash fluidity by blending with low viscosity coal. Both single coal and blended coal samples were studied to compare their ash fusion properties and viscosities. Thermodynamic calculations of slag contents were performed. Results revealed that the blended coals ash fusion temperatures differed little while their viscosities presented much difference. Viscosities of blended coal slags were similar at high temperature, however, the patterns of blended coal viscosity-temperature curve showed obvious divergence below 1450 °C. Thermodynamic calculations and X-ray diffraction results revealed that the content adequacy of mullite and quartz in the slag caused the solid phase separation from molten slag, which consequently resulted in the rapid increase in viscosity. The critical temperature and T25 of blended coals showed good linear dependence with blending ratio.